Habitual nocturnal sleep, napping behavior, and recovery following training and competition in elite water polo: Sex-related effects - Koutouvakis, N. G.; Geladas, N. D.; Mouratidis, A.; Toubekis, A. G.; Botonis, P. G. (International Journal of Sports Physiology and Performance, 2024)
Purpose To examine nocturnal sleep patterns, napping behaviors, and subjective wellness responses of elite water polo players within an in-season week and to identify whether sleeping patterns differ between men and women.